DISTRIBUTED ON-LINE TEMPERATURE MEASUREMENT and CONTROL SYSTEM - Hrusha, Volodymyr; Olexandr, Olexandr; Sachenko, Anatoly; Kochan, Roman (International Journal of Computing, 2014)
There is founded reasonability of implementation of measurement and control system with internet capability and proposed structure of its software in this paper. The main features of proposed structure are in its portability to system with different hardware structure. Also there is presented of investigation of dynamic characteristics of real time control system.